Unpacking food environment policy landscapes for healthier diets in “emerging” countries: the case of Viet Nam - Even, Brice; Truong, Thi Thu Trang; Thai, Thi Minh Hang; Pham, Thi Mai Huong; Nguyen, Thu Duong; Bui, Thi Viet Anh; Bene, Christophe (Frontiers Media, 2025)
Objective: Food systems and food environments are evolving rapidly in Viet Nam, concurrently with significant shifts in dietary patterns and health outcomes. This study aims to identify critical gaps in the national regulatory framework governing food environment in Viet Nam and to propose actionable recommendations to overcome these gaps. Results: Using the Food Environment Policy Index from the INFORMAS network, we mobilized a transdisciplinary panel of 18 experts to co-analyze and assess policy evidence, as well as co-develop policy recommendations. The assessment, encompassing 35 indicators across six food environment domains, revealed substantial gaps: 74% of indicators scored low or very low, while only 26% scored medium or high. Key gaps were identified in food composition standards, marketing, labeling, and financial incentives. Recommendations from the experts focused on strengthening food composition standards, enhancing consumer education, and fostering inter-sectoral policy integration. Implications: This study provides a comprehensive evaluation of Viet Nam’s food environment policies and offers actionable recommendations to foster food environments conducive of healthier diets. Drawing on Viet Nam as a case study representative of challenges in other low- and middle-income countries, our findings highlight the importance of strong political commitment to prioritize public health over industry interests in order to create healthier, more equitable food environments and food systems.